Travels to metropolitan London: experiences of two early twentieth-century Muslim women - Hasan, Md. Mahmudul (2019)
In September 1906, Atiya Fyzee (1877-1967) from India and Zeyneb Hanoum (1883-1923) from Turkey embarked on European tours and described their experiences in a chronological order in Zamana-e-Tahsil (A Time of Education [1921]) and A Turkish Woman’s European Impressions (1913), respectively. Fyzee visited England and Germany and Hanoum, France, Switzerland and England. In my comparative analysis of their travel experiences, I will focus on their representations of London and its people. Although they began their journeys from two separate locations, there are striking similarities in their birth and upbringing. Both were born in Istanbul. Although Fyzee lived in Bombay and died in Karachi, she was born in Istanbul and had family connection with the city. Both received western education and were passionate about women’s education and rights. Both seemed fascinated with London in their works though they were reluctant to call it “home”. However, there were also conspicuous differences in their circumstances and experiences. Fyzee was awarded a scholarship by the colonial British government to go to Britain to study Education (teacher training) at Maria Grey College in London, the first of its kind for women in England. Conversely, Hanoum along with her sister Melek Hanoum fled Turkey in order to escape restrictive conditions imposed on women in Sultan Abdul Hamid’s (r. 1876-1909) Turkey. Given these backgrounds and positionalities, I will discuss how Muslim women encountered Britain’s multicultural past and contributed to the intersection of host and diasporic communities in early twentieth-century London, the largest city in the world in the 1900s. I will contest the notions of harem and purdah in the context of Muslim societies, as Islam “prescribes travel for the purpose of hajj (pilgrimage), hijra (emigration) and rihla” or a journey to seek knowledge for both Muslim men and women. This research also marks a continuation of an earlier work – “Muslim Bengal writes back: A study of Rokeya’s encounter with and representation of Europe” (Journal of Postcolonial Writing, 2016) – where I discussed the encounter with Europe of Rokeya Sakhawat Hossain (1880-1932) who never visited the continent. In the current project, I will explore Muslim women’s experiences of Europe in Europe.